PERANCANGAN DAN PENGEMBANGAN PENCATATAN SURAT MASUK DAN KELUAR BERBASIS WEB DI KANTOR DESA LAROMABATI - Sukur, Rachmat Saleh; Umar, M. Kasyif Gufran (Universitas Teknokrat Indonesia, 2024)
North Kayoa County's Laromabati Village Office continues to take a traditional approach to managing incoming and outgoing mail. Each time a letter arrives or leaves, officers must manually record the letter's origin, date, and important details. After that, the officer must contact the intended party based on information about the origin of the letter. However, the recording process alone is not enough because incoming and outgoing mail documents are still saved manually. This condition often results in documents being scattered and hard to find when needed. Searching for documents is a complex task because it has to be done manually, searching for existing documents one by one.To solve this problem, as part of this study, you can develop an application to manage incoming and outgoing mail using a web platform. This application is designed to help ease the workflow, reduce the likelihood of incoming and outgoing emails, and make it easier to find incoming and outgoing emails.Based on the testing of the interface health monitoring system and the use of web applications, it was found that the application for recording incoming and outgoing letters in the village office of Laromabati, North Kayoa district was successfully created using the PHP programming language. . This application development uses the waterfall method as a development approach. The created application has the main function, namely to provide the benefit of a digital repository useful to the village administration, while simplifying the work process and reducing the risk of losing archives of incoming and outgoing letters. To test this application, two types of testing are conducted, namely black box testing and usability testing. The results of black box testing show that the application works without errors and meets the desired expectations.